Cystargamides C and D, New Cyclic Lipopeptides From a Tidal Mudflat-Derived Streptomyces sp. JMS132 - Seo, Jeongwon; Shin, Yern-Hyerk; Jo, Se Jin; Du, Young Eun; Um, Soohyun; Kim, Young Ran; Moon, Kyuho (Frontiers in Microbiology, 2022)
Cystargamides C and D (2 and 3) were isolated from a marine actinomycete strain collected at Beolgyo, Republic of Korea. The planar structures of the cystargamides were elucidated by 1/2D NMR, UV, and MS spectroscopic analyses. The absolute configurations of 2 and 3 were determined based on ROESY correlations and the advanced Marfey’s methods. The structures of the compounds were elucidated as new lipodepsipeptides bearing six amino acids with an epoxy fatty acid side chain. For the first time, the nonribosomal peptide synthetase biosynthetic pathway of the cystargamides has been proposed using whole genome sequence analysis. The cystargamides displayed antioxidant effect in the DPPH and ABTS assay.